New evidence for association of recessive IARS gene mutations with hepatopathy, hypotonia, intellectual disability and growth retardation. Issue 6 (19th October 2017) - Smigiel, R.; Biela, M.; Biernacka, A.; Stembalska, A.; Sasiadek, M.; Kosinska, J.; Rydzanicz, M.; Ploski, R.
Abstract :